Integrating experiences : body and mind moving between contexts - Wagoner, Brady, 1980-; Chaudhary, Nandita, 1957-; Hviid, Pernille (Niels Bohr professorship lectures in cultural psychology., 2015)
Cultural Psychology studies how persons and social-cultural worlds mutually constitute one another. It is premised on the idea that culture is within us--in every moment in which we live our human lives, in the meaningful worlds we have created ourselves. In this perspective, encounters with others fundamentally transform the way we understand ourselves. With the increase of globalization and multicultural exchanges, cultural psychology becomes the psychological science for the 21st century. No longer can we ignore questions about how our cultural traditions, practices, beliefs, artifacts and other people constitute how we approach, understand, imagine and remember the world. The Niels Bohr Professorship Lectures in Cultural Psychology series aims to highlight and develop new ideas that advance our understanding of these issues.This second volume in the series features an address by Tania Zittoun and Alex Gillespie, which is followed by commentary chapters and their response to them. In their lecture, Zittoun and Gillespie propose a model of the relation between mind and society, specifically the way in which individuals develop and gain agency through society. They theorise and demonstrate a two-way interaction: bodies moving through society accumulate differentiated experiences, which become integrated at the level of mind, enabling psychological movement between experiences, which in turn mediates how people move through society. The model is illustrated with a longitudinal analysis of diaries written by a woman leading up to and through the Second World War. Commentators further elaborate on the issues of (1) context and history, (2) experience, time and movement, and (3) methodologies for cultural psychology.